2022
DOI: 10.7554/elife.76854
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of transmission chains of SARS-CoV-2 amidst multiple outbreaks in a geriatric acute-care hospital: a combined retrospective epidemiological and genomic study

Abstract: Background:There is ongoing uncertainty regarding transmission chains and the respective roles of healthcare workers (HCWs) and elderly patients in nosocomial outbreaks of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in geriatric settings.Methods:We performed a retrospective cohort study including patients with nosocomial coronavirus disease 2019 (COVID-19) in four outbreak-affected wards, and all SARS-CoV-2 RT-PCR positive HCWs from a Swiss university-affiliated geriatric acute-care hospital t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Our study underscores the challenges of inferring group contributions in some scenarios, even in the hypothetical instance where transmission trees are perfectly known. Nevertheless, our approach is adaptable and can be extended to reconstructed transmission chains, for example, by estimating the assortativity coefficient across all posterior transmission trees in the setting of Abbas et al [15]. Future research should delve into understanding how uncertainty surrounding these transmission trees further impacts our ability to infer transmission patterns.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study underscores the challenges of inferring group contributions in some scenarios, even in the hypothetical instance where transmission trees are perfectly known. Nevertheless, our approach is adaptable and can be extended to reconstructed transmission chains, for example, by estimating the assortativity coefficient across all posterior transmission trees in the setting of Abbas et al [15]. Future research should delve into understanding how uncertainty surrounding these transmission trees further impacts our ability to infer transmission patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Our approach complements traditional survey-based methods when transmission chains are available. Worby et al .’s relative risk estimation [12], measuring each group’s proportional change in infection incidence before and after the peak, and Abbas et al .’s assessment method [15], comparing actual and expected proportions of infections across groups, do not consider the influence of group size. By integrating group size into our approach, we account for variations in the pool of susceptible individuals within each group, offering a more comprehensive understanding of transmission dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, a fatigued workforce and a market flooded with products of varying efficacy would prove to be new challenges for HEH. The disease also spread in unexpected ways; although it was expected that patients would be the cause of nosocomial spread, Covid-19 was often spread through the population of healthcare workers sharing lunch or carpooling to their patients [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Results from the first part of this study (September to December 2020) indicated transmission occurred mainly between children and among teachers within the school, with occasional spillover to their households [10]. Sequence data of rapidly evolving RNA viruses can provide valuable information on transmission events [11], as also illustrated specifically for SARS-CoV-2 [12]. In this study we make use of the whole genome sequences that were collected from September 2020 to June 2021 to aid in reconstructing the school outbreaks.…”
Section: Introductionmentioning
confidence: 99%